FINANCIAL PERFORMANCE ANALYSIS OF CV ARISKA PUTRI PERODE 2018-2021 - BUDI RAHMAN (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2023)
This research was conducted at companies operating in the construction sector of the building sector. The purpose of this research is to determine the effect of Net Profit Margin (NPM) and Total (TATO), partially and simultaneously to Return On Asset (ROA). The research population carried out by researchers was 1 company in the construction sector, the research sample was 48 with a 4 year period. Data analysis used in this research uses the Classical Assumption Test and Multiple Linear Regression Analysis as analytical tools which are processed with IBM SPSS 25 software. The results of research using Multiple Linear Regression are concluded that Net Profit Margin and Total Asset Turnover significant effect on Return on Asset. The results of research using multiple linear regression state that the Net Profit Margin variable has a significant effect on Return on Asset amounting to 7,687 and Total Assets Turnover amounting to 1.101, while the partial test also shows that both have an influence on the company's financial performance with the NPM value having a t value of 23.029 > 2.014 and a sig value of 0.000 < 0.05. Meanwhile, TATO has a tcount value of 7.687 > 2.014 and a sig value of 0.000 < 0.05. In simultaneous testing, values ​​are obtained Fcount amounting to 312,127. Value of Fcount 312,127>of Ftable 3.20 with a significant value of 0.000 < 0.05 means that simultaneously there is a significant influence on the variables Net Profit Margin (NPM) and Total Assets Turnover (TATO) on the company's financial performance. Overall, this research states that Net Profit Margin (NPM) and Total Assets Turnover (TATO) has a significant effect on CV's Financial Performance. Ariska Putri for the 2018-2021 period and this is of course also in accordance with the company's financial data and previous research theories that have been studied.